Comparing the Phylogenetic Distribution of Multilocus Sequence Typing, Staphylococcal Protein A, and Staphylococcal Cassette Chromosome Mec Types in Methicillin-Resistant Staphylococcus Aureus (MRSA) in Korea from 1994 to 2020 - You-Jin Hwang (MDPI AG, 2023)
Staphylococcus aureus (S. aureus) bacteremia is one of the most frequent and severe bacterial infections worldwide. Methicillin-resistant Staphylococcus aureus (MRSA) is a serious human pathogen that can cause a wide variety of infections. Comparative genetic analyses have shown that despite the existence of a vast number of genotypes, genotypes are restricted to certain geographical locations. By comparing multilocus sequence typing (MLST) and SCCmec types from 1994 to 2020, the present study intended to discover which genotype genes were related to MRSA infections. MLST, Staphylococcus aureus protein A (spa), and SCCmec typings were performed to determine their relationship during those years. Results revealed that MRSA isolates in the Republic of Korea were distributed among all major staphylococcal cassette chromosome mec (SCCmec) types. The majority of SCCmec isolates belonged to SCCmec type II and type IV. The majority of MLST had the sequence type (ST) 72, 239, 8, or 188. By contrast, minorities belonged to ST22 (SCCmec IV), ST772 (SCCmec V), and ST672 (SCCmec V) genotypes. The SCCmec type was determined for various types. The spa type was dispersed, seemingly regardless of its multidrug resistance property. The MLST type was found to be similar to the existing typical type. These results showed some correlations between resistance characteristics and types according to the characteristics of the MLST types distributed, compared to previous papers. Reports on genotype distribution of MLST and SCCmec types in MRSA are rare. These results show a clear distribution of MLST and SCCmec types of MRSA from 1994 to 2020 in the Republic of Korea.